Contextual factors associated with pain response of preterm infants to heel‐stick procedures. (2nd July 2012) - Sellam, G.; Engberg, S.; Denhaerynck, K.; Craig, K.D.; Cignacco, E.L.
Abstract Background Evidence indicates that medical and demographic contextual factors (cFs) impact pain responses in preterm neonates, but the existing evidence is very heterogeneous. Aim To explore the effect of cFs on pain responses to heel‐stick procedures of preterm infants. Methods This study was a secondary analysis of data collected during a randomized controlled trial examining pain response to non‐pharmacological interventions across repeated heel sticks. Five heel sticks across the first 14 days of life were videotaped. Pain response was rated with the Bernese Pain Scale for Neonates (BPSN) by four raters blinded to the heel‐stick phases (baseline, heel stick, recovery). Demographic and medical cFs were extracted from medical charts. Mixed single and multiple regression analyses were performed controlling for the intervention group, site and heel‐stick phase. Results Apgar scores at 1 min were negatively associated with behavioural (p = 0.002) BPSN scores, while Apgar scores at 5 min after birth were positively associated with behavioural (p = 0.006) scores. Accumulated number of painful procedures (p = 0.002) and gender (p = 0.02) were positively associated with physiological scores while continuous positive airway pressure CPAP (p = 0.009) and mechanical ventilation (p = 0.005) were negatively associated. Conclusion Higher exposure to painful procedures, male infants and having CPAP or mechanical ventilation were cFs associated with physiological response. The only variables significantly associated with behavioural BPSN scores were Apgar scores but these relationships were inconsistent.